Motion analysis of elite Polish soccer goalkeepers throughout a season - Szwarc, Andrzej; Jaszczur-Nowicki, Jaroslaw; Aschenbrenner, Piotr; Zasada, Mariusz; Padulo, Johnny; Lipinska, Patrycja (Biology of Sport, 2019)
The study aims were to determine the distance covered by goalkeepers during matches in the context of game duration and result, to identify the area of their most frequent activity, and to assess goalkeepers’ involvement in games finished with a win, draw, or loss. The investigation was based on two innovative tools: the goalkeeper’s activity index (GAI) and an analysis of 5-min periods. A video tracking system was used to monitor 17 goalkeepers from Polish National League teams during 15 matches. The GAI was applied to assess their involvement in the game. Elite goalkeepers covered 72.7%, 25.8%, and 2.5% of the distance during the game by walking/jogging, running, and sprinting, respectively. The distances covered in lost, won, and drawn matches turned out similar (mean ± SD: 4800 ± 906 m, 4696 ± 1033 m, and 4660 ± 754 m, respectively). There were no significant differences between the distances covered in the first and second halves. The area of most frequent activity was the middle sector of the penalty area between the goal and penalty area lines. ANOVA results showed that in drawn matches, goalkeepers’ activity significantly differed in mean values of the GAI in comparison with that in won and lost games (p = 0.034, p = 0.039, respectively). It was noted that goalkeepers tended to intervene more often in games where their team was winning rather than in those with a losing result. Their direct involvement in defending the goal was the lowest in drawn games.